Language and Literature : Spaces of intercultural Mediation. The performative Force of « Kuessipan » by Naomi Fontaine (Ponti/Ponts. Langues, littératures, civilisations des pays francophone, 2025)
The process of intercultural mediation aims to allow exchanges, connection, dialogue, rapprochement, understanding, prevention and resolution of disputes by postulating, as a fundamental value, the possibility of living together with differences (Cf. Paola Puccini, Michèle Vatz Laaroussi, Claude Gélinas, La Médiation interculturelle, Milan, Hoepli, 2022, pp. 21-22). It is therefore a matter of building a bridge between people, groups, institutions that are ignorant of each other, have prejudices or are in a situation of misunderstanding or conflict where the intercultural dimension is present, or even predominant. We believe that Indigenous literature is particularly significant in its attempt to denounce racism, discrimination, prejudice, exclusion and oppression, but also in its desire to draw up potential spaces for intercultural mediation to be developed. In our work we want to look at Kuessipan by Naomi Fontaine with the desire to show her performativity through which the author manages to create new spaces where she can stage the relationship between the members of a community and the world they live in build, thus generating a transformation. The pragmatics applied to the literary text and the linguistic theory of the enunciation will be used to describe the mechanisms of construction of links that are created beyond the barriers, exclusions, sufferings.
Keywords: Intercultural mediation; Linguistic theory of the enunciation; Indigenous literature; Kuessipan by Naomi Fontaine